Custodians of agrobiodiversity in Guinayangan, Quezon, Philippines - Duma, Jesus C.; Caringal, Ma. Isabel V.; del Rio, Susan P.; Anunciado, Ma. Shiela S.; Gonsalves, Julian F.; Monville-Oro, Emilita; Borelli, Teresa (Bioversity International and International Center for Tropical Agriculture, 2024)
This study assessed the diversity of crops, trees, and livestock managed by households in Guinayangan municipality, Quezon, Philippines. Over time, these households have acted as de facto custodians of biodiversity, even without explicitly aiming for conservation. Since the study began, households now appreciate the crops’ specific uses and their role in food security and local economies. Understanding the diversity of local varieties, breeds, and wild plants, along with their management and uses, is a vital first step toward ensuring their effective conservation and sustainable utilization.